Internet of Things Based Detection System for Pencak Silat PSHT Basic Technique Movements Using the Support Vector Machine Method - Ayunda Putri; Zara Yunizar; Muhammad Fikri; Fadlisyah; Hafiz Al Kautsar Aidilof (Lembaga Teewan Journal Solutions, 2026)
The utilization of technology in sports has become a crucial need to enhance modern coaching efficiency. In pencak silat, particularly within Persaudaraan Setia Hati Terate (PSHT), accurate mastery of basic techniques is essential. However, when students practice independently without supervision, they often struggle to ensure correct hand movements, lowering training quality and increasing injury risks. As a solution, this study develops a real-time, Internet of Things (IoT)-based hand movement monitoring system using Inertial Measurement Unit (IMU) sensors. The sensor data is processed via a Machine Learning approach utilizing a 7-SVM Pipeline architecture. The Support Vector Machine (SVM) algorithm is applied to Model 0 (Movement Classifier) for movement classification, and Models 1–6 (Correctness Classifier) to evaluate quality into